2014
DOI: 10.5489/cuaj.2170
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resident involvement in minimally-invasive urologic oncology procedures

Abstract: Introduction: Robotic and laparoscopic surgical training is an integral part of resident education in urology, yet the effect of resident involvement on outcomes of minimally-invasive urologic procedures remains largely unknown. We assess the impact of resident participation on surgical outcomes using a large multi-institutional prospective database. Methods: Relying on the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) Participant User Files (2005Files ( -2011, we abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 30 publications
4
21
0
2
Order By: Relevance
“…These findings corroborate previous reports that found RI to be significantly associated with pOT regardless of training status [16,17] . A significant association between RI and pOT was also found in more complex urological procedures as described by Ruhotina et al [17] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings corroborate previous reports that found RI to be significantly associated with pOT regardless of training status [16,17] . A significant association between RI and pOT was also found in more complex urological procedures as described by Ruhotina et al [17] .…”
Section: Discussionsupporting
confidence: 83%
“…Allard et al [16] showed that RI has no impact on overall complications or reoperation rates in endoscopic prostate surgeries and transurethral resection of bladder tumors, while readmission rates as quality of care measures were significantly higher in cases with RI. Along the same lines, 2 other studies focusing on RI in urological procedures reported no adverse outcomes following RI in reconstructive or minimally invasive procedures [17,24] .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The involvement of residents (including junior, senior, and chief residents) significantly increased the risk of an operative time >75 th percentile for minimally invasive partial and radical nephrectomies, as well minimally invasive radical prostatectomy. 4 Similarly, there was a twofold higher chance of a prolonged operative time (defined as >75% percentile) when urology residents were involved with transurethral surgery. 5 Among basic general surgery procedures (laparoscopic cholecystectomy or appendectomy, or open inguinal hernia repair, all of which tended to take approximately an hour), skin-to-skin operative time increased by 12-20 minutes with the involvement of both junior or senior residents, compared to the attending surgeon operating alone.…”
Section: Discussionmentioning
confidence: 99%
“…While non-teaching-based hospitals exist primarily to deliver patient care, academic hospitals have the additional demands of clinical research and the training and education of medical and nursing students, allied health professionals, and postgraduate physicians (interns, residents, and fellows). The inclusion of medical residents in surgical procedures performed in the U.S. has been shown to increase the risk of a prolonged operation for specific urological procedures (such as laparoscopic urological oncology procedures 4 and transurethral surgery 5 ), as well as in other surgical specialities (such as gynecology 6 and general surgery 7 ). The increase in operative duration associated with training future medical professionals inherently increases the operating room cost of procedures at academic hospitals and is not currently accounted for in many activity-based funding models.…”
Section: Introductionmentioning
confidence: 99%